Praktik SDM Berkelanjutan: Menelaah Hubungan antara Ketahanan Organisasi dan HRM Ramah Lingkungan di Sektor Perhotelan - I Nyoman Resa Adhika (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Organizations must adopt sustainable human resource practices (SHRP) to meet the difficulties of global sustainability. According to data published by the Official Statistics News, the number of foreign visitors to the province of Bali fluctuated. From July 2023 to November 2023, it dropped from 545,272 to 397,552, then increased to 502,830 until April 2024. All stakeholders in Bali Province, especially the hotel industry, must be able to pay attention to changes in the quantity of tourists visiting. This study investigates the effects of organizational resilience and Green Human Resource Management (GHRM) on SHRP in the hotel sector. 120 personnel from five-star hotels participated in the survey, which was carried out in Bali. The research problem was addressed with the aid of SEM PLS. The findings demonstrated that organizational resilience and GHRM significantly and favorably affect SHRP. According to the findings, the association is somewhat mediated by organizational resilience. This implies that the implementation of sustainable HR policies will be improved with the help of a strong GHRM policy and increased organizational resilience. The study’s practical implications include the need for hotels and other hospitality-related enterprises in Bali to implement more extensive GHRM policies, including environmentally-based performance evaluation, sustainability-focused training, and green hiring.